2003
DOI: 10.1007/s00125-003-1106-8
|View full text |Cite
|
Sign up to set email alerts
|

ACE-inhibitors but not endothelin receptor blockers prevent podocyte loss in early diabetic nephropathy

Abstract: Aims/hypothesis. It was the aim of our study to investigate the influence of a selective ET-A receptor antagonist LU 135252 alone and in combination with the ACE-inhibitor, trandolapril on podocyte number and morphology in streptozotocin diabetic rats. Methods. Male Sprague-Dawley rats were injected with 65 mg streptozotocin i.v. and subsequently developed diabetes. Animals were left untreated or received daily either trandolapril (0.3 mg/kg body weight), LU 135252 (50 mg/kg body weight) or a combination of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(31 citation statements)
references
References 38 publications
(45 reference statements)
0
29
1
1
Order By: Relevance
“…It is possible that in less severely affected patients, only diseased podocytes with low WT-1 expression are shed into the urine, while in patients with advanced diabetic nephropathy, even ‘normal’ podocytes with preserved WT-1 expression are lost. It should be noted that previous studies on urinary podocytes usually focus on the level of podocyte loss rather than the qualitative change of the podocytes being shed [36,37,38]. Because the number of subjects in this study was small, we cannot exclude the possibility that the urinary mRNA expression of other podocyte-associated molecules may also be correlated with the degree of histological damage.…”
Section: Discussionmentioning
confidence: 61%
“…It is possible that in less severely affected patients, only diseased podocytes with low WT-1 expression are shed into the urine, while in patients with advanced diabetic nephropathy, even ‘normal’ podocytes with preserved WT-1 expression are lost. It should be noted that previous studies on urinary podocytes usually focus on the level of podocyte loss rather than the qualitative change of the podocytes being shed [36,37,38]. Because the number of subjects in this study was small, we cannot exclude the possibility that the urinary mRNA expression of other podocyte-associated molecules may also be correlated with the degree of histological damage.…”
Section: Discussionmentioning
confidence: 61%
“…Zhang et al [17] found that losartan, perindopril, and captopril could block high glucose induced hypertrophy in rat proximal tubular cells. Gross et al [18] found that trandolapril could prevent podocyte hypertrophy and degeneration in STZ-induced diabetic rats and, consequently, prevent the development of albuminuria. Studies had shown that AngII induced proliferation requiring a complete cell progression through the various steps of the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Each score reflects changes in the extent rather than the intensity of staining and depends on the percentage of positive glomeruli. The degree of MDA and NDUFS3 expression in ten rats from each group was graded as follows: 0, absent or !25% staining; 1, 25-50% positive staining; 2, 50-75% positive staining; and 3, more than 75% positive staining (Gross et al 2003).…”
Section: Immunohistochemistry Stainingmentioning
confidence: 99%